2021
DOI: 10.1109/access.2021.3135012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Tracking Rotations Using Maximal Entropy Distributions for Smartphone Applications

Abstract: Recursive attitude estimation of a rigid body from inertial measurements is a crucial component of many modern systems and as such, has a rich historical background of proposed techniques. Recent work has been done on tracking rotations using maximal entropy distributions. However, there has been no evaluation done on the performance of this approach using real inertial data. In this work, we investigate the performance and limitations of classical and modern probabilistic Bayesian approaches and provide a rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In [ 24 ], the authors present TLIO, again using ResNet, to regress 3D displacement estimates and the uncertainty, allowing them to tightly fuse the relative state measurement into a stochastic cloning extended Kalman filter (EKF) to solve for pose, velocity and sensor biases. Owing to its reliance on an EKF, it was shown to be susceptible to a system failure during highly dynamic or unusual motion, which is in line with previous work [ 25 ]. Similarly, in [ 26 ], the authors propose a hybridised approach using an LSTM and EKF in a modular design that consists of orientation and position subsystems, termed IDOL.…”
Section: Related Worksupporting
confidence: 86%
“…In [ 24 ], the authors present TLIO, again using ResNet, to regress 3D displacement estimates and the uncertainty, allowing them to tightly fuse the relative state measurement into a stochastic cloning extended Kalman filter (EKF) to solve for pose, velocity and sensor biases. Owing to its reliance on an EKF, it was shown to be susceptible to a system failure during highly dynamic or unusual motion, which is in line with previous work [ 25 ]. Similarly, in [ 26 ], the authors propose a hybridised approach using an LSTM and EKF in a modular design that consists of orientation and position subsystems, termed IDOL.…”
Section: Related Worksupporting
confidence: 86%
“…A GRU was built, as previous work has shown that it outperforms Temporal Convolutions Networks and other RNN variants [32]. Additionally, we use a UKF, proven effective in attitude estimation in previous work [6].…”
Section: Baselinesmentioning
confidence: 99%
“…Most of the complexity in attitude estimation stems from its nonlinearity, and therefor its estimation solution must account for the nonlinear dynamics in the system. Early applications relied on the extended Kalman filter (EKF) to linearise the dynamic system about the current best-state estimate; however, this process can yield poor performance particularly in highly dynamic situations due to divergence and constant reinitialisation [6]. These difficulties led to the development of alternative filters, several of which retain the basic structure of the EKF; most notably the Unscented Kalman Filter (UKF) which, at the time of writing, is the industry standard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation